Native CGRP Neuropeptide and Its Stable Analogue SAX, But Not CGRP Peptide Fragments, Inhibit Mucosal HIV-1 Transmission - Mariotton, Jammy; Sams, Anette; Cohen, Emmanuel; Sennepin, Alexis; Siracusano, Gabriel; Sanvito, Francesca; Edvinsson, Lars; Delongchamps, Nicolas Barry; Zerbib, Marc; Lopalco, Lucia; Bomsel, Morgane; Ganor, Yonatan (Frontiers in Immunology, 2021)
Background: The vasodilator neuropeptide calcitonin gene-related peptide (CGRP) plays both detrimental and protective roles in different pathologies. CGRP is also an essential component of the neuro-immune dialogue between nociceptors and mucosal immune cells. We previously discovered that CGRP is endowed with anti-viral activity and strongly inhibits human immunodeficiency virus type 1 (HIV-1) infection, by suppressing Langerhans cells (LCs)-mediated HIV-1 trans-infection in-vitro and mucosal HIV-1 transmission ex-vivo. This inhibition is mediated via activation of the CGRP receptor non-canonical NFκB/STAT4 signaling pathway that induces a variety of cooperative mechanisms. These include CGRP-mediated increase in the expression of the LC-specific pathogen recognition C-type lectin langerin and decrease in LC-T-cell conjugates formation. The clinical utility of CGRP and modalities of CGRP receptor activation, for inhibition of mucosal HIV-1 transmission, remain elusive. Methods: We tested the capacity of CGRP to inhibit HIV-1 infection in-vivo in humanized mice. We further compared the anti-HIV-1 activities of full-length native CGRP, its metabolically stable analogue SAX, and several CGRP peptide fragments containing its binding C-terminal and activating N-terminal regions. These agonists were evaluated for their capacity to inhibit LCs-mediated HIV-1 trans-infection in-vitro and mucosal HIV-1 transmission in human mucosal tissues ex-vivo. Results: A single CGRP intravaginal topical treatment of humanized mice, followed by HIV-1 vaginal challenge, transiently restricts the increase in HIV-1 plasma viral loads but maintains long-lasting higher CD4+ T-cell counts. Similarly to CGRP, SAX inhibits LCs-mediated HIV-1 trans-infection in-vitro, but with lower potency. This inhibition is mediated via CGRP receptor activation, leading to increased expression of both langerin and STAT4 in LCs. In contrast, several N-terminal and N+C-terminal bivalent CGRP peptide fragments fail to increase langerin and STAT4, and accordingly lack anti-HIV-1 activities. Finally, like CGRP, treatment of human inner foreskin tissue explants with SAX, followed by polarized inoculation with cell-associated HIV-1, completely blocks formation of LC-T-cell conjugates and HIV-1 infection of T-cells. Conclusion: Our results show that CGRP receptor activation by full-length CGRP or SAX is required for efficient inhibition of LCs-mediated mucosal HIV-1 transmission. These findings suggest that formulations containing CGRP, SAX and/or their optimized agonists/analogues could be harnessed for HIV-1 prevention.